The protective role of Lactobacillus rhamnosus GG postbiotic on the alteration of autophagy and inflammation pathways induced by gliadin in intestinal models - Furone, Francesca; Bellomo, Claudia; Carpinelli, Martina; Nicoletti, Martina; Hewa-Munasinghege, Francesca Natasha; Mordaa, Majed; Mandile, Roberta; Barone, Maria Vittoria; Nanayakkara, Merlin (Frontiers in Medicine, 2023)
Celiac disease (CD) is an autoimmune enteropathy caused by an abnormal immune response to gliadin peptides in genetically predisposed individuals. For people with CD, the only available therapy thus far is the lifelong necessity for a gluten-free diet (GFD). Innovative therapies include probiotics and postbiotics as dietary supplements, both of which may benefit the host. Therefore, the present study aimed to investigate the possible beneficial effects of the postbiotic Lactobacillus rhamnosus GG (LGG) in preventing the effects induced by indigested gliadin peptides on the intestinal epithelium. In this study, these effects on the mTOR pathway, autophagic function, and inflammation have been evaluated. Furthermore, in this study, we stimulated the Caco-2 cells with the undigested gliadin peptide (P31-43) and with the crude gliadin peptic-tryptic peptides (PTG) and pretreated the samples with LGG postbiotics (ATCC 53103) (1 × 108). In this study, the effects induced by gliadin before and after pretreatment have also been investigated. The phosphorylation levels of mTOR, p70S6K, and p4EBP-1 were increased after treatment with PTG and P31-43, indicating that the intestinal epithelial cells responded to the gliadin peptides by activating the mTOR pathway. Moreover, in this study, an increase in the phosphorylation of NF-κβ was observed. Pretreatment with LGG postbiotic prevented both the activation of the mTOR pathway and the NF-κβ phosphorylation. In addition, P31-43 reduced LC3II staining, and the postbiotic treatment was able to prevent this reduction. Subsequently, to evaluate the inflammation in a more complex intestinal model, the intestinal organoids derived from celiac disease patient biopsies (GCD-CD) and controls (CTR) were cultured. Stimulation with peptide 31-43 in the CD intestinal organoids induced NF-κβ activation, and pretreatment with LGG postbiotic could prevent it. These data showed that the LGG postbiotic can prevent the P31-43-mediated increase in inflammation in both Caco-2 cells and in intestinal organoids derived from CD patients.